Metafora Dalam Lirik Lagu Album Berhati Karya Sal Priadi - Zikri Alfiya; Indra Perdana; Lazarus Linarto; Albertus Purwaka; Misnawati Misnawati (Universitas Palangka Raya, 2023)
The purpose of this research is to describe (1) the types of metaphors found in the lyrics of the album